ANALISIS KOMPARATIF PENDAPATAN USAHATANI SAYURAN DI DESA TANJUNG KARI KECAMATAN PULAU BERINGIN KABUPATEN OKU SELATAN (JASEP, 2018)
Comparison of Vegetable Farming Income in Tanjung Kari Village, Pulau Beringin Subdistrict, South Ogan Komering Ulu Regency. This study aims to compare the income of vegetable farmers between patterns in Tanjung Kari Village, Pulau Beringin District, OKU Selatan Regency, conducted in December 2016 until January 2017. The research was conducted in Tanjung Kari Village, Beringin Island, South Ogan Komering Ulu Regency. The research method used in this research is survey method. Sampling method is done by saturation sampling because the population is less than 30. The population is 23 population and all the population is used as sample. Based on the research, it can be concluded that the income of vegetable farmers on the pattern I of Rp 4,326,950 per planting season is greater than the income of the II pattern of Rp 2,533,112.5 per planting season and the third pattern is Rp 3,852,256.25 per planting season.